Exploring the capacity of community‐based organisations to absorb health system patient referrals for unmet social needs. (27th July 2020) - Hogg‐Graham, Rachel; Edwards, Katie; L. Ely, Todd; Mochizuki, Malinda; Varda, Danielle
Abstract: This study examines the perspectives, resources, role and services provided by community‐based organisations (CBOs) in response to the integration of health and social services to address individual unmet social needs, as well as the impact on organisational carrying capacity related to the ability to receive referrals from health system partners. Mixed methods combining qualitative interviews with 24 organisations and Social Network Analysis with 75 organisations were completed in 2018 in two communities (Denton, TX and Sarasota, FL) with robust examples of health and social systems alignment. Findings suggest that while community organisations are embedded in robust cross‐sector networks, the potential increase in referrals from clinical settings is not something they are fully aware of, or prepared for, as evidenced by inadequate funding models, misalignment between capacity and capability, and a lack of coordination on screening and referral activities. Misalignment between clinical and CBO understanding of demand, needs and capacity present a potential risk in building strategies that integrate health and social services to address unmet social need. Failing to build a strong cross‐sector screening and referral infrastructure that considers CBO capacity from the start could undermine the goal of improving population health through the integration of clinical and social care.